Mutant Isocitrate Dehydrogenase 1 Inhibitor Ivosidenib in Combination With Azacitidine for Newly Diagnosed Acute Myeloid Leukemia. Issue 1 (1st January 2021) - DiNardo, Courtney D.; Stein, Anthony S.; Stein, Eytan M.; Fathi, Amir T.; Frankfurt, Olga; Schuh, Andre C.; Döhner, Hartmut; Martinelli, Giovanni; Patel, Prapti A.; Raffoux, Emmanuel; Tan, Peter; Zeidan, Amer M.; et al.
Abstract : PURPOSE: Ivosidenib is an oral inhibitor of the mutant isocitrate dehydrogenase 1 (IDH1) enzyme, approved for treatment of IDH1 -mutant (m IDH1 ) acute myeloid leukemia (AML). Preclinical work suggested that addition of azacitidine to ivosidenib enhances mIDH1 inhibition–related differentiation and apoptosis. PATIENTS AND METHODS: This was an open-label, multicenter, phase Ib trial comprising dose-finding and expansion stages to evaluate safety and efficacy of combining oral ivosidenib 500 mg once daily continuously with subcutaneous azacitidine 75 mg/m 2 on days 1-7 in 28-day cycles in patients with newly diagnosed m IDH1 AML ineligible for intensive induction chemotherapy (ClinicalTrials.gov identifier: NCT02677922 ). RESULTS: Twenty-three patients received ivosidenib plus azacitidine (median age, 76 years; range, 61-88 years). Treatment-related grade ≥ 3 adverse events occurring in > 10% of patients were neutropenia (22%), anemia (13%), thrombocytopenia (13%), and electrocardiogram QT prolongation (13%). Adverse events of special interest included all-grade IDH differentiation syndrome (17%), all-grade electrocardiogram QT prolongation (26%), and grade ≥ 3 leukocytosis (9%). Median treatment duration was 15.1 months (range, 0.3-32.2 months); 10 patients remained on treatment as of February 19, 2019. The overall response rate was 78.3% (18/23 patients; 95% CI, 56.3% to 92.5%), and the complete remission rate was 60.9% (14/23 patients; 95% CI, 38.5% to 80.3%). With median follow-up of 16 months, median duration of response in responders had not been reached. The 12-month survival estimate was 82.0% (95% CI, 58.8% to 92.8%). m IDH1 clearance in bone marrow mononuclear cells by BEAMing (beads, emulsion, amplification, magnetics) digital polymerase chain reaction was seen in 10/14 patients (71.4%) achieving complete remission. CONCLUSION: Ivosidenib plus azacitidine was well tolerated, with an expected safety profile consistent with monotherapy with each agent. Responses were deep and durable, with most complete responders achieving m IDH1 mutation clearance.